2023
DOI: 10.3390/ph16030342
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Punica granatum L. Leaves Extracts as a Source of Bioactive Molecules

Abstract: Due to a lack of innovative valorization strategies, pomegranate processing generates a significant amount of residues with a negative environmental footprint. These by-products are a rich source of bioactive compounds with functional and medicinal benefits. This study reports the valorization of pomegranate leaves as a source of bioactive ingredients using maceration, ultrasound, and microwave-assisted extraction techniques. The phenolic composition of the leaf extracts was analyzed using an HPLC-DAD-ESI/MSn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…For instance, Yan H et al [ 40 ] reported that polyphenols in pomegranate peel accelerated wound healing in diabetic mice by increasing fibroblast infiltration, collagen regeneration, and vascularization/epithelialization in the wound area. Recently, Marcelino et al [ 41 ] found that exposure to bioactive compounds extracted from pomegranate leaves at concentrations of 50 to 400 μg/mL increased the viability of human fibroblasts by >70% and of keratinocytes by >50% at the highest concentrations. In a rat study, the application of hydrogels enriched with ellagic acid to wounds contaminated with Staphylococcus aureus and Escherichia coli reduced the wound area, inhibited infection, and promoted angiogenesis and collagen deposition [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Yan H et al [ 40 ] reported that polyphenols in pomegranate peel accelerated wound healing in diabetic mice by increasing fibroblast infiltration, collagen regeneration, and vascularization/epithelialization in the wound area. Recently, Marcelino et al [ 41 ] found that exposure to bioactive compounds extracted from pomegranate leaves at concentrations of 50 to 400 μg/mL increased the viability of human fibroblasts by >70% and of keratinocytes by >50% at the highest concentrations. In a rat study, the application of hydrogels enriched with ellagic acid to wounds contaminated with Staphylococcus aureus and Escherichia coli reduced the wound area, inhibited infection, and promoted angiogenesis and collagen deposition [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, identified compounds in HPLC-MS analysis have exhibited properties that benefit skin health, such as antimicrobial, antioxidant, anti-inflammatory, chemoprotective, cytotoxic, and wound-healing properties [ 49 , 50 , 51 , 52 ]. Therefore, these compounds may be responsible for the observed biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] The resistance problem can be addressed by the development of innovative agents with different modes of action to avoid cross-resistance with current therapeutics. [7] Therefore, new classes of antibacterial agents with new mechanisms are critically needed to combat multidrug-resistant infections. Several azole derivatives have been recently developed as new antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%